Ischemic Stroke Updates - Schaller, Bernhard (IntechOpen, 2016)
This book covers all aspects and the most vibrant topics of ischemic stroke research: from basic sciences to latest methods of clinical applications. The authors give an overview of what has importance today in stroke research and also strike future ideas. The diversity of origin of the internationally known authors underlines not only that ischemic stroke research is nowadays global but also that this diversity gives new and valuable inputs to treat our patients.